Epigenetic-based combination therapy and liposomal codelivery overcomes osimertinib-resistant NSCLC via repolarizing tumor-associated macrophages - Lin Ting-ting; Xiong Wei; Chen Gui-hua; He Yang; Long Li; Gao Xin-fu; Zhou Jia-lin; Lv Wen-wen; Huang Yong-zhuo (Acta Pharmacologica Sinica; Vol 45, No 4 (April 2024): Acta Pharmacologica Sinica, 2024)
Osimertinib (Osi) is widely used as a first-line treatment for non-small cell lung cancer (NSCLC) with EGFR mutations. However, the majority of patients treated with Osi eventually relapse within a year. The mechanisms of Osi resistance remain largely unexplored, and efficient strategies to reverse the resistance are urgently needed. Here, we developed a lactoferrin-modified liposomal codelivery system for the combination therapy of Osi and panobinostat (Pan), an epigenetic regulator of histone acetylation. We demonstrated that the codelivery liposomes could efficiently repolarize tumor-associated macrophages (TAM) from the M2 to M1 phenotype and reverse the epithelial-mesenchymal transition (EMT)-associated drug resistance in the tumor cells, as well as suppress glycolysis, lactic acid production, and angiogenesis. Our results suggested that the combination therapy of Osi and Pan mediated by liposomal codelivery is a promising strategy for overcoming Osi resistance in NSCLC.